Data resource profile: the Edinburgh Child Protection Dataset - a new linked administrative data source of children referred to Child Protection paediatric services in Edinburgh, Scotland - Marryat, Louise; Stephen, Jacqueline; Mok, Jacqueline; Vincent, Sharon; Kirk, Charlotte; Logie, Lindsay; Devaney, John; Wood, Rachael (International Journal of Population Data Science, 2023)
Introduction Child maltreatment affects a substantial number of children. However current evidence relies on either longitudinal studies, which are complex and resource-intensive, or linked data studies based on social services data, which is arguably the tip of the iceberg in terms of children who are maltreated. Reliable, linked, population-level data on children referred to services due to suspected abuse or neglect will increase our ability to examine risk factors for, and outcomes following, abuse and neglect. Objective The objective of this project was to create a linkable population level dataset, The Edinburgh Child Protection Dataset (ECPD), comprising all children referred to the Edinburgh Child Protection Paediatric healthcare team due to a concern about their welfare between 1995 and 2015. Methods The paper presents the process for creating the dataset. The analyses provide examples of available data from the main referrals dataset between 1995 and 2011 (where data quality was highest). Results 19,969 referrals were captured, relating to 11,653 children. Of the 19,969 referrals, a higher proportion were girls (54%), although boys were referred for physical abuse more often than girls (41% versus 30%). Younger children were more likely to be referred for physical abuse (35% of 0-4 year olds vs. 27% 15+): older children were more likely to be referred for sexual abuse (48% of 15+ years vs. 18% of 0-4 years). Most referrals came from social workers (46%) or police (31%). Conclusions The ECPD offers a unique insight into the characteristics of referrals to child protection paediatric services over a key period in the history of child protection in Scotland. It is hoped that by making these data available to researchers, and able to be easily linked with both mother and child current and future health records, evidence will be created to better support maltreated children and monitor changes over time.